The Effects of Qur’an-Based Differentiated Mathematics Instruction on Academic Achievement and Religious Character: The Role of Students’ Learning Styles at MAN 2 Wonosobo - Siti Ngarofah; Maryono; Jumini; M. Yusuf Amin Nugroho; Nia Natasya; Ahmad Najih Musoffa Fuadi; Arim Irsyadulloh Albin Jaya; Dyah Ayu Fitriana (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aimed to analyze: (1) the effect of Qur’an-based differentiated mathematics instruction on students’ academic achievement and religious character; (2) the effect of learning styles on students’ academic achievement and religious character; and (3) the interaction between Qur’an-based differentiated mathematics instruction and learning styles in influencing students’ academic achievement and religious character. This study employed a quantitative approach with a factorial design. The population consisted of Grade X students at MAN 2 Wonosobo. Using simple random sampling, 69 students from four randomly selected classes were included in the sample. The experimental classes received Qur’an-based differentiated mathematics instruction adapted to students’ learning styles, whereas the control classes received conventional instruction. Data were collected through an academic achievement test and a religious character questionnaire and were analyzed using two-way ANOVA with SPSS 25. The findings showed that: (1) Qur’an-based differentiated mathematics instruction had a significant effect on students’ academic achievement and religious character; (2) students’ learning styles significantly affected academic achievement and religious character; and (3) a significant interaction existed between Qur’an-based differentiated mathematics instruction and learning styles in relation to academic achievement and religious character. These findings indicate that Qur’an-based differentiated mathematics instruction tailored to students’ learning styles is effective in improving academic outcomes and fostering religious character. The study provides practical implications for teachers to implement differentiated instructional strategies grounded in Qur’anic values on a sustained basis and for schools to support the development of instructional models responsive to students’ learning styles.